PERBEDAAN HASIL BELAJAR BAHASA INDONESIA SISWA INDONESIA SISWA YANG MENGIKUTI BIMBINGAN BELAJAR DAN YANG TIDAK MENGIKUTI BIMBINGAN BELAJAR DI SMA NEGERI 1 KISARAN KELAS XI IPA TAHUN AJARAN 2012/2013 - SRI GANTINI (Universitas Negeri Medan, 2012)
This study aims to determine the differences in the results of study Indonesian students studying in counseling with students who do not follow the guidance of class XI science student SMAN 1 range learning year 2012/2013. The population of all students in grade XI SMA Negeri 1 range learning year 2012/2013. Samples were taken at random technique as many as 60 people and divided into 2 groups. The first group of students who participated tutoring and group into two groups that did not participate tutoring. The method used in this research is cooperative, with multiple-choice tests as a means of gathering research data. Based on the research data that cooperative learning outcomes of students who participated tutoring had an average value of 70.33 and the learning outcomes of students who did not participate tutoring had an average value of 58.83. The results of the analysis of normality test results to learn Indonesian language students who did not participate tutoring can be seen that the price to test 0.1220 L count lilifors N = 30 with a real level α = 0.05 in the table can be L = 1.1610. after the comparison turns count L <L table or 0.1220 <0.1610 which means that the data are normally distributed, while for the tutoring take note that the price was 0.1493 with L count liliforn test with N = 30 and the real level α = 0.05 to L in table = 1.1610. after the comparison turns count <L tables or 0.1493 <0.1610 which means that the data are normally distributed. To test the hypothesis to (5.78) t table (2.00), which means that to> thitung the nil hypothesis (Ho) is rejected and the alternative hiotesis (Ha) is accepted. This proves that there is a significant difference outcomes study Indonesian students who attend tutoring with students who did not participate tutoring. Keywords: learning outcomes, totoring, tutoring agencies.